A study of efficacy and safety of high-intensity focused ultrasound for the treatment of melasma in Asians: A single-blinded, randomized, split-face, pilot study - Vasanop Vachiramon (2020)
© 2019 Wiley Periodicals, Inc. Background: A recent report suggested potential of high-intensity focused ultrasound in improving UVB-induced hyperpigmentation in patients with Fitzpatrick skin type IV, but reports regarding its efficacy in other hyperpigmented conditions including melasma are lacking. Objectives: To investigate efficacy and safety of high-intensity focused ultrasound for the treatment of melasma in Asians. Methods: Each side of the face of 25 melasma patients was randomized to receive 3-monthly sessions of high-intensity focused ultrasound treatment or serve as control. Lightness index, Melasma Area and Severity Index of malar area (MASIm) by blinded dermatologists, self-evaluated improvement and satisfaction scales by patients, and side effects were assessed every 4 weeks for 20 weeks. Results: Twenty-one patients with Fitzpatrick skin type III and IV completed the study. There was a greater reduction of relative lightness index and MASIm after treatment in high-intensity focused ultrasound-treated side. However, there were no statistically significant differences between both sides. More than 50% improvement on treatment side was rated in 11 patients (52.4%). Side effects were minimal. None had worsening of melasma. Conclusions: High-intensity focused ultrasound may be an adjuvant for treatment of melasma. Further studies with larger sample size and proper parameter settings are recommended to determine its efficacy.